Synthesis, Thermal, and Optical Properties of Tris(5‐aryl‐1, 3, 4‐oxadiazol‐2‐yl)‐1, 3, 5‐triazines, New Star‐Shaped Fluorescent Discotic Liquid Crystals. Issue 67 (4th November 2019) - Tober, Natalie; Rieth, Thorsten; Lehmann, Matthias; Detert, Heiner
Abstract: The synthesis of tris(aryloxadiazolyl)triazines (TOTs), C 3 ‐symmetrical star‐shaped mesogenes with a 1, 3, 5‐triazine center, 5‐phenyl‐1, 3, 4‐oxadiazole arms, and various peripheral alkoxy side chains is reported. Threefold Huisgen reaction on a central triazine tricarboxylic acid and suitable aryltetrazoles yields the title compounds. Selected analogues with a benzene center are included in this study and allow for an evaluation of the impact of the central unit on the physical properties. Thermal (differential scanning calorimetry, DSC; polarization optical microscopy, POM), optical (UV/Vis, fluorescence), electric (time of flight, TOF), and structural (single crystal; wide‐angle X‐ray scattering, WAXS) properties of these compounds were investigated. The modification of alkoxy chain length and substitution pattern allows for a tuning of the physical properties. TOTs emit blue to yellow light, depending on conjugation length, donor–acceptor substitution, and solvent polarity, whereas concentration quenches and aggregation enhances the emission. The width of the mesophases is typically around Δ T =100–150 K but can even exceed 220 K. Polarization optical microscopy and X‐ray diffraction on oriented filaments reveal that TOTs are highly ordered liquid crystals (LCs) with long‐range hexagonal columnar structure. Abstract : Disco(tic) stars : A series of C 3 ‐symmetrical stars is prepared through the Huisgen reaction of alkoxyaryltetrazoles and a central tricarboxylic acid. These π‐conjugated discotic molecules are solvatochromic fluorophores, a rim of six to nine alkoxy chains causes broad mesophases.